Pemanfaatan Intranet Sebagai Sarana Informasi di Epistema Institute - Septia, Ririn; Ruhimat, Ruhimat; Taufiq, M Aries; Hidayati, Hidayati (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2023)
Abstract Intranet is a private network owned by a company or organization that functions as a medium for sharing confidential information for a company or organization with its employees or employees. Intranet is a communication medium for all employees in an effort to increase work productivity and effectiveness, as well as a sense of belonging and a sense of kinship among members of the organization, especially at the episteme institute. The purpose of this study is to find out and understand how the use of the intranet as a means of information at the Epistema Institute. This study uses Karl Weick's organizational information theory, in which this theory discusses how the dissemination of information has an important role in an organization to maintain the continuity of its activities. This theory focuses on the process of collecting, managing and using information carried out by individuals in accordance with procedures established by the organization to process information sent and received. The results of the research show that using the Intranet as a means of information based on cyber-PR at the Epistema Institute must integrate with various divisions within the organization. Each division within the organization has a main focus on its main tasks, but the goals of the organization also need to be a concern for all divisions so adjustments need to be made to the tasks of each division. Division of the Epistema Institute needs other divisions to obtain additional information as a whole.Keyword : Intranet, Internal Communication, Karl Weick's TheoryAbstraksi Intranet merupakan jaringan privat yang dimiliki perusahaan atau organisasi yang berfungsi sebagai media untuk membagikan informasi yang bersifat rahasia bagi perusahaan atau organisasi kepada pegawai atau karyawannya. Intranet merupakan salah satu media komunikasi bagi seluruh karyawan dalam upaya meningkatkan produktivitas dan efektivitas kerja, serta rasa memiliki maupun rasa kekeluargaan dalam di antara anggota organisasi, khususnya di epistema institute. Tujuan dari penelitian ini adalah untuk mengetahui dan memahami bagaimana pemanfaatan intranet sebagai sarana informasi di epistema institute. Penelitian ini menggunakan teori informasi organisasi Karl Weick, dimana dalam teori ini dibahas bagaimana penyebaran informasi memiliki peranan yang penting dalam sebuah organisasi untuk tetap dapat terjaga keberlangsungan aktivitasnya. Teori ini menitikberatkan pada proses pengumpulan, pengelolaan dan pemanfaatan informasi yang dilakukan oleh individu sesuai dengan prosedur yang ditetapkan organisasi untuk mengolah informasi yang dikirim dan diterimaHasil penelitian menunjukkan dalam pemanfaatan Intranet sebagai sarana informasi yang berbasis cyber-PR di Epistema Institute harus saling berintegrasi dengan berbagai divisi dalam organisasi. Masing-masing divisi di dalam organisasi memiliki fokus utama pada tugas utamanya, namun tujuan dari organisasi juga perlu menjadi perhatian bagi semua divisi sehingga perlu dilakukan penyesuaian pada tugas divisi masing-masing. Setiap divisi dalam Epistema Institue membutuhkan divisi lain untuk memperoleh tambahan informasi sebagai satu kesatuan.Keyword : Intranet, Komunikasi internal, Teori Karl Weick